Ultra‐Low Power Corrosion Sensor Made of Iron Nanowires on Magnetic Tunnel Junctions. Issue 10 (1st August 2018) - Mashraei, Yousof; Amara, Selma; Albu, Zahra; Ivanov, Yurii P.; Kosel, Jürgen
Abstract : Corrosion sensors are of critical importance for monitoring the destructive potential of a corrosive environment. Due to their large surface‐to‐volume area, nanowires react with a remarkably high speed, rendering them attractive corrosion‐sensing elements. To avoid the difficulties related to contacting nanowires, the authors present a magnetic approach, exploiting the fast reaction of nanowires to the environment. Iron nanowires have a high magnetization value, which decreases upon nanowire corrosion. Due to shape anisotropy, they also possess a large remnant magnetization, which is detectable by a magnetic tunnel junction sensor. Iron nanowires are fabricated by electrochemical deposition, placed on top of the magnetic tunnel junction and aligned using a magnetic field. The nanowires provide a bias field causing a change of the characteristic curve of the tunnel junction. The corrosion sensor is tested in a saline solution, where the nanowires corroded, leading to a reduction of the bias field and restoration of the original characteristic. Combined, the nanowires and tunnel junction realize a highly integrated sensor concept that enables corrosion sensing with an ultra‐low power consumption of less than 1 nW, a sensitivity of 0.1%/min, a response time of 30 min and a sensor area of only 128 μm 2 . Abstract : A magnetic tunnel junction with magnetic iron nanowires on top of it is used for corrosion sensing. The nanowires react fast to a corrosive environment, due to the large surface‐to‐volume ratio. The corrosion affects the magnetic properties of the nanowires, which are measured by the energy‐efficient MTJ sensor.